HUBUNGAN PENGETAHUAN ORANG TUA DENGAN RAMPAN KARIES (Poltekkes Kemenkes Bandung, 2022)
Dental caries is a disease that has a high prevalence in Indonesian society, dental caries in early childhood will affect the development of permanent tooth growth and interfere with aesthetics. The prevalence of caries is related to bottle feeding children throughout the day and parental knowledge. The purpose of this study was to determine the relationship between parental knowledge and rampant caries in Andria children in Sumedang Regency.This research is an analytic survey with a cross sectional design which aim to determine the relationship between parental knowledge and rampant caries in Andria children in Sumedang Regency. The sample was 35 children and their parents who were examined for rampant caries and their level of knowledge was measured. Data analysis using Pearson Chi-square correlation test with hypothesis testing with 95% confidence level. The results showed that there was a relationship between parental knowledge and rampant caries in kindergarten children (p value = 0.02 <0.05). Parents are expected to pay attention to the health of their teeth and mouth, and guide their children in brushing their teeth. Key words: rampan caries, parental knowledge, children